Fully discrete error estimation for a quasi-Newtonian fluid–structure interaction problem. (June 2016) - Lee, Hyesuk; Xu, Shuhan
Abstract: We consider an incompressible quasi-Newtonian fluid–structure interaction (FSI) problem formulated in a monolithic framework, where the matching conditions at the moving interface are satisfied. The fully discretized FSI system is discussed with detailed analysis for the stability and error estimate as well as numerical experiments that confirm the theoretical results.